FEUDAL HERITAGE : SOURCE OF CORRUPTION, COLLUSION, AND NEPOTISM - Suhartono Suhartono (Faculty of Cultural Sciences, Universitas Gadjah Mada, 1999)
The political development in Indonesia at the present time has been marked by a terminology of change, namely